Mitral valve surgery in severe congenital factor VII deficiency. Issue 1 (January 2014) - Syburra, Thomas; Siciliano, Raffaele Daniele; Hofer, Christoph; Genoni, Michele
<x content-type="archive" xml:space="preserve">Abstract</x> The estimated incidence of congenital factor VII deficiency is 1:500 000. Severe FVII deficiency is associated with spontaneous bleeding such as intraarticular or intracranial haemorrhage. The risk of perioperative bleeding is high during cardiac surgery as a result of the exposure to extracorporeal circulation, systemic anticoagulation, loss of coagulation factors, and postoperative platelet malfunction. Effective treatment of pre-existing coagulopathy is crucial, as increased morbidity and mortality are associated with allogenic blood transfusions. We report a 67-year-old Caucasian male patient with severe congenital FVII deficiency, undergoing successful and uneventful elective mitral valve repair surgery, radiofrequency epicardial atrial fibrillation ablation, and exclusion of the left atrial appendage. He presented with severe symptomatic mitral valve regurgitation, moderate pulmonary artery hypertension, and paroxysmal atrial fibrillation; his left ventricular ejection fraction was 67%. Three years before surgery, during a routine assessment of a grade I renal failure, a spontaneous International Normalised Ratio of 4.1 was observed. He had no history of previous spontaneous bleeding. The diagnosis of a severe FVII deficiency, with an FVII activity below 2% (normal references values in City Hospital Triemli Zurich: 55–170%) was made.